Examining the psychometric properties of the deputy-principal mentoring questionnaire - Hassan, Roslizam; Mohd Tahir, Lokman; Musah, Mohammed Borhandden; Abdul Aziz, Norazah; Hamzah, Lina Mursyidah; Hasnor, Hanin Naziha; Ahmad, Roslee (International Journal of Evaluation and Research in Education (IJERE), 2024)
This article intends to inspect and validate the Malay language version of the self-developed instrument on informal leadership mentoring used by principals with their deputy principals in the Malaysian primary school context. This article relies on the survey responses by 318 Malaysian primary deputy principals. Descriptively, the responses to all 25 items produced high mean scores which indicated that deputy principals are well-satisfied with the mentoring and guidance provided to improve their leadership prowess. Based on exploratory factor analysis, three factors emerged: guidance, informal approaches, and substituting principals in official meetings. However, the third factor was removed because it was only represented by one item. Thus, there are two major factors: guidance and informal approaches with 24 items, all of which had high factor-loading values and were consistent in their internal validity. In addition, the average variance extracted and composite reliability were also calculated which received acceptable values. Lastly, the confirmatory factor analysis (CFA) results indicated that all 24 items achieved acceptable values.